Pendidikan Multikultural di SMAN 1 Masalembu Sumenep (Studi Pada Mata Pelajaran Pendidikan Agama Islam Aspek Fiqh) - Arifin, Miftahol (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
The variety of culture in small islands of Sumenep regency has some uniqueness to be observed. For instance, the ethnic group in Masalembu island consist of Bugis, Mandar, Button, Bajo, Java and Madurese. That culture variety (multiculture) need an education innovation especially in Islamic education at Masalembu Junior High School 1 Sumenep. Multiculture education is a learning way that is oriented to the process of making personality and attitude of students to make them understand about plurality, equality, and tolerance to others in the society. Furthermore, the writer try to observe about Multiculture Education at Masalembu Junior High School 1 Sumenep through a teaching model to Islamic education subject of Fiqh side which the students condition is vary in ethnic groups and culture. This research is a qualitative field research using descriptive approach. The data collection in this research using observation, interview, and documentation. The result of the research shows that Multiculture Education through acomodative strategy is a learning process that give knowledge to the students about culture, tradition, attitude patterns in society and become an identity for future progress of individually and the society itself. Through this teaching strategy Multiculture Education can be applied in Masalembu Junior High School 1 Sumenep. Acomodative Learning Model at Masalembu Junior High School 1 Sumenep has a clear lesson plan, so that students able to have appreciatiation and positive impact to the students who has different culture in the classroom and able to understand the culture variety in their society. The students’ appreciation in the classroom shows that they have pluralist attitude. There is no differences or similarity and tolerance to their friends inside or outside the classroom. Whereas, the appreciation of students to the society shows that the students able to understand the differences between Islamic education of Fiqh side that they received at school and the plurality of culture in their society.